Identification of 'wasteful commuting' using search theory - Jos Van Ommeren; J. Willemijn Van der Straaten (European Regional Science Association (ERSA), 2005)
In this paper, we employ search theory as a micro-economic foundation for the wasteful commuting hypothesis. In the empirical analysis, the extent of the 'wasteful commuting' is identified by comparing the commute of employees and self-employed individuals who do not work from home. It is argued that the commute of the self-employed is the result of a search process for vacant workplaces, whereas employees search for vacant jobs. Because the arrival rate of workplaces exceeds the arrival rate of jobs, the self-employed have a shorter commute. We find that 35% of the commuting time may be considered 'wasteful' and reject alternative hypotheses why the self-employed have a shorter commute.
Keywords: 330